2015
DOI: 10.2319/030514-156.1
|View full text |Cite
|
Sign up to set email alerts
|

Tooth-borne vs bone-borne rapid maxillary expanders in late adolescence

Abstract: For patients in late adolescence, bone-borne expanders produced greater orthopedic effects and fewer dentoalveolar side effects compared to the hyrax expanders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
287
3
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(327 citation statements)
references
References 18 publications
25
287
3
12
Order By: Relevance
“…3,12,20 In contrast, clinical crown heights were not significantly different in the treatment and posttreatment periods in this study ( Figure 6). Gingival recession of , 0.21 mm to 0.52 mm was not clinically significant during orthodontic treatment with MARME, which was in accordance with the findings of Lin et al 11 Use of the miniscrew could distribute the stress throughout the palate, decreasing the concentration of the stress around the anchor teeth. 17 To overcome the retrospective nature of this study, all attempted cases were collected and followed regardless of the treatment outcome.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…3,12,20 In contrast, clinical crown heights were not significantly different in the treatment and posttreatment periods in this study ( Figure 6). Gingival recession of , 0.21 mm to 0.52 mm was not clinically significant during orthodontic treatment with MARME, which was in accordance with the findings of Lin et al 11 Use of the miniscrew could distribute the stress throughout the palate, decreasing the concentration of the stress around the anchor teeth. 17 To overcome the retrospective nature of this study, all attempted cases were collected and followed regardless of the treatment outcome.…”
Section: Discussionsupporting
confidence: 80%
“…7 Recently, successful maxillary skeletal expansion with a tooth-bone-borne RME device based on miniscrews (miniscrew-assisted RME [MARME]) was introduced 7 and is based on previous findings that the true bony obliteration of the midpalatal suture in radiographs does not correlate with chronological age. [8][9][10] Lin et al 11 reported that bone-anchored RME produced greater orthopedic effects and fewer dentoalveolar side effects compared with conventional RME in late adolescents. Taken together, it appeared crucial to incorporate bone anchorage to secure the expansion of the maxillary basal bone.…”
Section: Introductionmentioning
confidence: 99%
“…The most pronounced mean increase of the SNA angle by 2.17°was, interestingly, seen in the hybrid subgroup of skeletal Class III patients, indicating that hybrid RME appliances may indeed be advantageous in these patients, possibly due to skeletal effects related to their direct anchorage in the bony maxilla [47].…”
Section: Discussionmentioning
confidence: 92%
“…Another anchorage type combines teeth with jawbone [45,68], resulting in so-called hybrid RME appliances [68] that combine formal and design elements of the strictly tooth-borne (conventional) and the strictly bone-borne variants [51]. The latter, due to their anchorage in maxillary bone, reportedly have more pronounced skeletal effects than strictly tooth-borne designs [47], which could be desirable notably in the treatment of Class III or, specifically, maxillary retrognathism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a study evaluating the differences between C-expander and Hyrax expander (a type of tooth-borne expander), and they found that there was less alveolar bending, less dental tipping, and less vertical alveolar bone loss at the first premolar (the anchorage teeth of Hyrax expander) in C-expander group. 5 But because of its acrylic pads, C-expander has the same soft-tissue irritation problem with Haas expander. 6 Therefore, we introduce a new type of expander (spike expander) without acrylic pads, which is more hygienic and prevents soft-tissue irritation caused by food impaction under the acrylic plate.…”
mentioning
confidence: 99%